“Supplying the public with a comprehensive telegraph system”: Switzerland and telegraphic communication, 1860-1915 - Wenzlhuemer, Roland (Global Europe - Basel papers on Europe in a global perspective, 2014)
Historical research has recently discovered its interest in the study of transregional and global networks of communication and their significance for the so-called “shrinking of the world”. In this context, the emergence and the role of a global telegraph network since the middle of the nineteenth century has started to attract scholarly attention. The foundations of this network have mostly been laid by actors from the United Kingdom, the United States, and other important colonial powers. The role of smaller European or non-European states and their position in the emerging global network has rarely been examined. Switzerland usually only enters this discussion as the host of the International Telegraph Union (ITU), which played a decisive role in the development of international telegraphic standards. However, Switzerland’s role within the network and the ways Swiss actors made use of telegraphic communication during the nineteenth century have not been studied so far. This study seeks to fill this gap by examining the development of telegraphy in Switzerland as well as the position of the country within a wider European and global communication network. It looks at a number of markers regarding telegraphic development in Switzerland, both from a structural and from a use perspective. The overall goal is to test how well-developed the Swiss telegraph network was during the period of observation and how the country compares to other European (and some non-European) countries. It aims to shed light on how Switzerland was structurally integrated into a wider European and global network, and on how intensively the existing infrastructure was put to use. Furthermore, the study aims to reveal what other countries across the globe the Swiss chose to communicate with telegraphically.